A study on the feasibility of using local starch sources in culture media - Brual, Cary Bruce C. (Manila College of Pharmacy, University of the Philippines, 1994)
A chemically defined solid culture media was tried to be developed in this study using starch isolated from gabi, kamote, and kamoteng kahoy. Proteins isolated from soy beans (misu) and ammonium dihydrogen phosphate were used as sources of nitrogen. Thiamine, nicotinic acid and Revicon Forte were used as vitamin supplements. Sodium chloride and potassium hydrogen phosphate were the mineral source. Staphylococcus aureus and Escherichia coli were the microorganisms used representing the gram-positive and gram-negative organisms, respectively.
This study gave negative results for all of the media formulations made. It is possible that starch was not converted to simpler units by the test microorganisms used thus were not able to utilize starch as an energy food and as a carbon source. The inability of the microorganisms to digest the starch may be explained by the inadequate secretion of amylase and maltase, which are responsible for breaking down starch into glucose by the microorganisms. Starch should be converted to glucose in order to be utilized by microorganisms.
Other microorganisms should be tested, using the different variables used in this study, to determine the suitability of the formulation with them.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, September 1994.
Keywords: Microbiology--Cultures and culture media; Cassava; Taro; Starch